Emotion-Focused Therapy as a Humanistic Framework for Semi-Military Vocational Education - Hasbi, Hasbi; Neviyarni, Neviyarni; Netrawati, Netrawati; Hariko, Rezki (Southeast Asian Journal of Technology and Science, 2025)
Semi-military vocational education is increasingly questioned due to concerns about its impact on students’ autonomy, emotional well-being, and personal development, despite its effectiveness in fostering discipline and order. This conceptual article aims to propose Emotion-Focused Therapy (EFT) as a humanistic framework to humanize semi-military vocational education without diminishing its disciplinary strengths. Using a critical literature review approach, this study synthesizes theoretical and empirical insights from militaristic education models, humanistic education perspectives, and EFT principles to construct an integrative conceptual framework. The analysis reveals that semi-military educational environments tend to prioritize obedience and control, often at the expense of emotional expression, creativity, and student agency. The findings suggest that integrating EFT principles, such as emotional awareness, empathetic teacher, student relationships, emotional regulation, and supportive authority, can create a more balanced educational climate. This framework positions educators as caring mentors while maintaining structured discipline, thereby promoting resilience, self-awareness, and emotional competence among vocational students. The article concludes that EFT-informed humanistic practices offer a viable and ethical pathway to reform semi-military vocational education, with practical implications for curriculum development, teacher training, and institutional policy.